Optimal taxation when the tax burden matters - Robin Jessen; Maria Metzing; Davud Rostam-Afschar (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
Survey evidence shows that the magnitude of the tax liability plays a role in value judgements about which groups deserve tax breaks. We demonstrate that the German tax-transfer system conflicts with a welfarist inequality averse social planner. It is consistent with a planner who is averse to both inequality and high tax liabilities. The tax-transfer schedule reflects non-welfarist value judgements of citizens or different aims of policy makers. We extend our analysis to several European countries and the USA and show that their redistributive systems can be rationalized with an inequality averse social planner for whom the tax burden matters. – – Umfragen zeigen, dass die Höhe der Steuerschuld eine Rolle bei der Beurteilung der Frage spielt, welche Gruppen Steuererleichterungen verdienen. Wir zeigen, dass das deutsche Steuertransfersystem im Widerspruch zu einem welfaristischen, ungleichheitsfeindlichen sozialen Planer steht. Es ist konsistent mit einem Planer, der sowohl Ungleichheit als auch hohen Steuerbelastungen gegenüber abgeneigt ist. Das Steuer-Transfer-System spiegelt nicht-welfaristische Werturteile der Bürger oder unterschiedliche Ziele der politischen Entscheidungsträger wider. Wir erweitern unsere Analyse auf mehrere europäische Länder und die USA und zeigen, dass deren Umverteilungssysteme mit einem ungleichheitsaversen sozialen Planer, für den die Steuerlast eine Rolle spielt, in Einklang stehen.
Keywords: D63; D60; H21; H23; I38; 330; Justness; optimal taxation; income redistribution; inequality; welfare criteria